Social innovation, financialisation and commodification: a critique of social impact bonds. Issue 1 (2nd January 2021) - Sinclair, Stephen; McHugh, Neil; Roy, Michael J.
ABSTRACT: Despite a lack of evidence of their effectiveness there is increasing enthusiasm for Social Impact Bonds (SIBs) from diverse political perspectives across the world. This paper argues that while SIBs may potentially be applicable to some technical policy interventions which address relatively simple conditions, they are inappropriate for the complex conditions characterising wicked social problems. Enthusiasm for and over-extension of SIBs reflects a simplistic view of "evidence-based" policy. More fundamentally, SIBs commodify citizens and redefine service users as problems and potential revenue sources rather than conscious agents. SIBs therefore exemplify a prevalent ideology of marketisation and financialisation in social policy.